2007
DOI: 10.1002/eat.20403
|View full text |Cite
|
Sign up to set email alerts
|

Activities of respiratory chain complexes in isolated platelets in females with anorexia nervosa

Abstract: Objective: A broad spectrum of endocrine and biochemical disturbances was observed in patients with anorexia nervosa. In addition, metabolic changes may concern the efficiency of mitochondrial energy generating system. In our study we analyzed the activities of respiratory chain complexes in females with anorexia nervosa.Method: The activities of respiratory chain complexes I, II, IV, I 1 III, and citrate synthase serving as the control enzyme were measured spectrophotometrically in isolated platelets in 36 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The activities of respiratory chain Complexes I and II in isolated platelets were signifi cantly higher in females with anorexia nervosa in comparison with control group. No differences were found in the activities of Complexes IV, I+III, and citrate synthase (39).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The activities of respiratory chain Complexes I and II in isolated platelets were signifi cantly higher in females with anorexia nervosa in comparison with control group. No differences were found in the activities of Complexes IV, I+III, and citrate synthase (39).…”
Section: Discussionmentioning
confidence: 74%
“…The study of physiological and pathological mitochondrial function is essential for the diagnostics and targeting therapy of mitochondrial diseases. It was shown that circulating platelets can act as sensors of the infl ammatory and metabolic stresses associated with various chronic diseases, as cardiovascular disease, neurodegenerative diseases and diabetes (39). The respirometry of human platelets allows dynamic monitoring of mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining mitochondrial function are typically measured in permeabilized skeletal muscle fibers. However, platelet mitochondria have been established as well suited for ex vivo analysis of cellular respiration (Sjövall et al 2010, Hroudová et al 2013) and the activity of respiratory chain complexes (Böhm et al 2007). Platelets are an easily obtainable source of viable mitochondria and disturbances in the function of platelet mitochondria have been demonstrated in aging (Merlo Pich et al 1996, Lenaz et al 2000, Xu et al 2007) and in variety of diseases, including neurodegenerative disorders (Krige et al 1992, Hauptmann et al 2006, Shi et al 2008, Hroudová et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of energy supply in the patients with anorexia nervosa may be compensated by a higher efficiency of ATP production. In adult females with anorexia nervosa, Böhm and coworkers [28] suggest a higher efficiency of the respiratory complexes I and II in isolated Table 3 Coenzyme Q10 in juveniles (n 5 16) with anorexia nervosa at the time points of admission to and discharge from the children's hospital platelets, but the authors suggest normal activity of complexes III and IV which probably contests the facility of an increased total capacity in oxidative phosphorylation in patients suffering from anorexia nervosa. An inhibition of mitochondrial energy metabolism is supposed for inborn errors of metabolism like methyl malonyl aciduria (MMA).…”
Section: Discussionmentioning
confidence: 95%